Analysis of Workload of Cireng Production Workers Using The Nasa-TlX Method at UD. Mitra Abadi Maduran - Ainur Rohman Fatikh, Muhammad; Abdullah, Ishlahuddin (Indonesian Journal of Engineering, Science and Technology, 2025)
This study aims to analyze the workload experienced by workers in the production of snow cireng and chicken-filled cireng at UD Mitra Abadi, Duriwetan Village, Maduran Subdistrict, Lamongan. The production process involves high physical and mental demands, especially in activities such as manually mixing dough, shaping dough, lifting raw materials, and performing packaging. The NASA Task Load Index (NASA-TLX) method is used to measure perceived workload based on six dimensions, namely mental demand, physical demand, time pressure, effort, level of success, and level of frustration. Data collection was obtained through observation, interviews, and distributing questionnaires to workers. The results of the study show that the workers' workload level falls into the high category, with the indicators most influencing the workload being Effort (27.50%) and Physical Demand (22.50%), which indicates that production activities require significant physical effort and are performed repeatedly, making it the most dominant factor causing fatigue. Some workers also complain of discomfort in the back, shoulders, and arms due to manual work and less ergonomic working postures. Recommended improvements include adding male workers so tasks do not overlap and the workload is reduced, as well as adding automatic mixing machines to decrease physical fatigue. The use of PPE such as heat-resistant gloves should be mandatory, and the layout and height of worktables need to be adjusted to be more ergonomic and reduce physical complaints. Keywords- Workload; NASA-TLX Method; Ergonomics.